Nutcracker Syndrome as a Rare Cause of Hematuria and Left Flank Pain - Israel Darío Carrillo Quisnia; Cristian Xavier Muñoz Peralvo; Steffy Mishell Falconí Cobeña; Carlos Santiago Acosta Peralvo (Medisur)
Nutcracker syndrome is a rare cause of pelvic pain and flank pain, with associated hematuria, orthostatic proteinuria, varicocele in men, and ovarian and pelvic varices in women. The objective of this research was to provide updated information on the nutcracker syndrome as a cause of left flank pain associated with hematuria for its timely diagnosis and management. A systematic bibliographic review was carried out. Different scientific documents were consulted in databases such as: Pubmed, Scielo, Medline and Science Direct. The most frequently reported symptoms have traditionally been left flank pain along with gross or microscopic hematuria. For an adequate diagnosis, it should be noted that the first diagnostic tool is the physical examination. If the patient has symptoms of pelvic congestion and hematuria. It can be confirmed by diagnostic imaging studies.